2013
DOI: 10.1152/ajpcell.00374.2012
|View full text |Cite
|
Sign up to set email alerts
|

The human Cx26-D50A and Cx26-A88V mutations causing keratitis-ichthyosis-deafness syndrome display increased hemichannel activity

Abstract: Mutations in the human gene encoding connexin 26 (Cx26 or GJB2) cause either nonsyndromic deafness or syndromic deafness associated with skin diseases. That distinct clinical disorders can be caused by different mutations within the same gene suggests that different channel activities influence the ear and skin. Here we use three different expression systems to examine the functional characteristics of two Cx26 mutations causing either mild (Cx26-D50A) or lethal (Cx26-A88V) keratitis-ichthyosis-deafness (KID) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 50 publications
(91 reference statements)
3
70
0
Order By: Relevance
“…Connexin hemichannels have long been considered as merely structural precursors, yet compelling evidence in the last few years clearly shows that hemichannels autonomously form a pathway of communication, albeit not between neighboring cells, as is the case for gap junctions, but between the cytosol of individual cells and their extracellular environment. In fact, not only dysregulated gap junctional communication, but also aberrant connexin hemichannel activity has been observed in a number of skin diseases [28][29][30][31]. Several authors have reported Cx43 modulation in human diseases related to poor skin healing, such as hypertrophic scars and keloids [11] or in wounds of diabetic patients [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Connexin hemichannels have long been considered as merely structural precursors, yet compelling evidence in the last few years clearly shows that hemichannels autonomously form a pathway of communication, albeit not between neighboring cells, as is the case for gap junctions, but between the cytosol of individual cells and their extracellular environment. In fact, not only dysregulated gap junctional communication, but also aberrant connexin hemichannel activity has been observed in a number of skin diseases [28][29][30][31]. Several authors have reported Cx43 modulation in human diseases related to poor skin healing, such as hypertrophic scars and keloids [11] or in wounds of diabetic patients [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Even among patients with KID syndrome, there is a strongly dichotomous genotype-phenotype correlation [40]. Patients with Cx26-D50N, the most common mutation, live into adulthood, and clinical concerns include vascularizing keratitis causing blindness, and development of squamous cell carcinomas in chronically inflamed skin [68, 69].…”
Section: Human Epidermal Disorders Caused By Connexin Mutationsmentioning
confidence: 99%
“…Cx30 forms voltage-gated hemichannels (Valiunas and Weingart, 2000), which are normally closed under physiological conditions and open in response to low extracellular concentrations of Ca 2+ and Mg 2+ (De Vuyst et al, 2007;Tong et al, 2007;Verselis and Srinivas, 2008). Importantly, leaky hemichannels that result in cell death have been reported for a number of other connexin mutations (Gerido et al, 2007;Lee et al, 2009;Mese et al, 2011;Stong et al, 2006) and also for the A88V Cx26 mutation, which is linked to KID syndrome (Mhaske et al, 2013). The crystal structure of Cx26 suggests that part of the…”
Section: The A88v Mutant Linked To Clouston Syndromementioning
confidence: 99%